A promoção do direito fundamental à saúde: a aplicação da medicina de precisão via Big Data e Blockchain na oncopediatria - Teixeira, Estéfani Luise Fernandes (2022)
This dissertation is part of the line of research: Constitutional Jurisdiction and Democracy. The problem question is: how can precision medicine applied using Big Data and Blockchain in the pediatric oncology sector promote the fundamental right to health, especially within the scope of the SUS? The 1988 Federal Constitution recognizes health as a fundamental social right of every human being and requires the State to provide the necessary conditions for promoting actions aimed at improving health in Brazil. Society is facing a new moment, whose changes are related to the use of technologies, and the reflection of these new paradigms in law cannot be ignored. Advances in technology change the world, making it necessary to reflect on the fundamental right to health and technology. Thus, it intends to examine the influences of economically viable technological advances in the Brazilian health sector, notably in the Unified Health System - SUS, for the effective applicability of supreme constitutional values. In this segment, implementing technologies such as Big Data and Blockchain, providing precision medicine, is essential to guarantee decent health for patients and to protect fundamental rights and guarantees arising from them, set out in the Federal Constitution of 1988. In this sense, the proposition of public policies that are innovative, effective and efficient is crucial to the provision of health services that respect the dignity of the population. Thus, recognizing the essential imposition of compliance with fundamental rights and guarantees and, mainly, the fundamental principle of human dignity, in the present study, is a fundamental assumption for the development/improvement of any human relationships, especially those involving health. Therefore, it reflects measures to structure a society with fair equality of opportunities in the health sector, as well as the active action of the government to achieve a Democratic Rule of Law established by CRFB/88. In methodological terms, it used the deductive approach, whose analysis technique will be based on bibliographic and documentary research, and the Brazilian legal system from CRFB/88. Finally, the methodology proposed to achieve the objectives is hypothetical-deductive with an exploratory nature and carried out through a bibliographical survey. The method of legal interpretation is sociological, combining with the procedural method functionalist to analyze the role that the fundamental right to health plays in the pursuit of a fairer society in terms of opportunities.